Small screen and big screen: Mobile film-making in Australasia. Issue 1 (1st October 2013) - Schleser, Max R. C.; Wilson, Gavin; Keep, Dean
Over the past decade, technological advances have enabled the transformation of mobile phones with built-in cameras into sophisticated digital media tools (smartphones), capable of recording, editing and sharing high definition video content across global communication networks. Advances in smartphone technologies, and in particular increased lens quality, data memory and improved camera functionality, have arguably contributed to the emergence of a new kind of film-maker who recognizes and exploits the creative potential presented by camera phones. In this article, the authors will examine the challenges and perceived opportunities for film-makers using camera phones in an Australasian media context, including the ways in which camera phones may facilitate innovative practices around the production, sharing and viewing of digital films. The subsequent emergence of dedicated festivals for the screening of video content captured on camera phones is driving interest in new forms, new genres and new practices in film-making. We outline ways in which these festivals provide 'amateur' and independent film-makers, along with audiences, with a vital platform to initiate discussion, debate and the sharing of video content produced by film-makers from culturally diverse backgrounds.